THE EFFECT OF PQRST METHOD ON STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT - Lamhot Simatupang; Lince Sihombing (Universitas Negeri Medan, 2012)
This study was aimed to find out the effect of PQRST Method on students’ reading comprehension. There were sixty students, then they divided into two groups namely experimental and control group. The control was taught by conventional method while experimental group was taught by PQRST Method. The researcher used Kuder-Richardson (KR-21) formula to obtain the reliability of the test.. The calculation showed the reliability was 0.91 (high). The data were analyzed by using t-test. The calculation showed t-observed (2.80) is higher than t-table (2.000) at the level of significance (µ) 0.05 with the degree of freedom (df) 58. Therefore, null hypothesis (ha) is accepted. It means that PQRST Method has significantly affects students’ reading comprehension of descriptive text. Key words: PQRST Method, Reading Comprehension.